Clays and Clay Minerals, Vol. 55, No. 5, 504–518, 2007. - Aldega, Luca; Botti, Flavia; Corrado, Sveva (The Clay Minerals Society, 2007)
Temperature-dependent clay mineral assemblages and vitrinite reflectance data have been used to investigate levels of diagenesis from the Messinian Laga Basin in the Central Apennines developed at the footwall of the Sibillini Mts. and the Gran Sasso Massif. Data are from stratigraphic units forming the main siliciclastic basin fill up to Middle Messinian gypsum-arenites and its pre-orogenic substratum. Specifically, the largest Rom% values and percentages of illite layers in illite-smectie (I-S) are found in the basin depocenter and at the footwall of the main carbonate thrust sheets. Smaller Rom% values, and percentage of illite layers in I-S characterize less subsided sectors surrounding the depocenter. The X-ray diffraction data were treated using decomposition methods and the peaks identified were rationalized in terms of discrete and/or mixed-layer phases. Complex clay mineral assemblages were found in the Laga Fm. including three sub-populations of illitic material corresponding to authigenic and detrital components. I-S mixed layers record the maximum paleotemperature the Laga Fm. experienced, which is directly related to its burial history. Ku¨ bler index (KI) data, however, suggest higher temperatures related to detrital K-micas inherited from the uplift of the Alpine-Apennines chain. A tentative calculation of paleotemperatures from selected data of organic and inorganic parameters is also proposed and compared with recent sedimentological, stratigraphic and structural data. We conclude that the Laga Basin fill never experienced temperatures of >100-110ºC, generally due to variable sedimentary loading, whereas localized anomalous heating is due to the effect of the tectonic emplacement and subsequent local erosion of the Sibillini and Gran Sasso thrust sheets.
Clay Mineral Assemblages And Vitrinite Reflectance In The Laga Basin (central Apennines, Italy): What Do They Record?
Clays and Clay Minerals, Vol. 55, No. 5, 504–518, 2007. Clay Mineral Assemblages And Vitrinite Reflectance In The Laga Basin (central Apennines, Italy): What Do They Record? Luca Aldega; Flavia Botti; Sveva Corrado. DOI: 10.1346/CCMN.2007.0550505. Copyright © 2007, The Clay Minerals Society
Keywords: Periodicals; Geology; Illite; Italy; Ku¨bler Index; Laga Basin; Mixed-layer Clay Minerals; Syn-orogenic Deposits; Thermal Evolution; Vitrinite Reflectance